2014
DOI: 10.1039/c3ra46645k
|View full text |Cite
|
Sign up to set email alerts
|

Pristine organo-imido polyoxometalates as an anode for lithium ion batteries

Abstract: . (2014). Pristine organo-imido polyoxometalates as an anode for lithium ion batteries. RSC Advances: an international journal to further the chemical sciences, 4 (15), 7374-7379. Pristine organo-imido polyoxometalates as an anode for lithium ion batteries AbstractHere we have designed a strategy to improve the electronic conductivities of polyoxometalates (POMs) via property-oriented organic grafting for use in lithium-ion batteries (LIBs). POMs usually exhibit limited electronic conductivity that hinders the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Therefore, in order to achieve the practical applications of LIBs in EVs, there are numerous efforts on seeking for high performance anode materials that possess high capacity and excellent stability with long cyclic life [5][6][7]. Metallic tin (Sn) is considered as a potential substitute for conventional graphite anode (372 mAh/g) due to its high theoretical capacity (992 mAh/g) and thermal stability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in order to achieve the practical applications of LIBs in EVs, there are numerous efforts on seeking for high performance anode materials that possess high capacity and excellent stability with long cyclic life [5][6][7]. Metallic tin (Sn) is considered as a potential substitute for conventional graphite anode (372 mAh/g) due to its high theoretical capacity (992 mAh/g) and thermal stability [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Grafted POMs with nanotubes, [53,54] carbon black, [55] graphene, [51,56] or organic groups to generate ac onducting POM matrix had been attested to be a practical strategy to improvet he cycle stabilitya nd cycle performance. [52] Of all the previous studies, nanocarbon materials (especially carbon nanotubes and graphene) show ap ossibility to incooperate POMs wellt o www.chemasianj.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim meet the challengesi ne nergy storage, as it not only enhances the conductivity of the pure POMs buta lso restrains the POMs' volumee xpansion during the chargea nd discharge process (Table 1). [52] Of all the previous studies, nanocarbon materials (especially carbon nanotubes and graphene) show ap ossibility to incooperate POMs wellt o www.chemasianj.org 2018 Wiley-VCH Verlag GmbH &Co. KGaA, Weinheim meet the challengesi ne nergy storage, as it not only enhances the conductivity of the pure POMs buta lso restrains the POMs' volumee xpansion during the chargea nd discharge process (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Khan et al have designed a unique method to improve the conductivity by grafting the electron donating groups on the POM cluster. [194] They functionalized hexamolybdate with three different groups, -SCN with electron withdrawing affinity, -H with no effect on electronic flow and -CH 3 with electron donating effect to explore the hypothesis that by tuning the electronic density of POM their performance can be boosted up. It is found that after grafting all these groups, the capacitive performance of hexamolybdate has improved due to the structural stability or electronic disturbance.…”
Section: Metal-organic Complexes As Anode Materialsmentioning
confidence: 99%